A rare case report: unruptured ovarian pregnancy - Sarkar, Shipra; Ghosh, Somenath; Mitra, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Ovarian pregnancy is a rare form of ectopic pregnancy. Its incidence is 0.5-1% of all ectopic gestations or 1 in 7000 to 40000 live births. The diagnosis is intricate and based on surgical and histopathological observations. In our institute in last 10 years, we have seen a single confirmed case out of 189 ectopic pregnancies. It was a spontaneous pregnancy with no history of contraception failure and diagnosed as tubal ectopic by ultrasound imaging. Laparotomy findings and histopathology confirmed it to be an Ovarian Pregnancy.